ASSESSMENT OF WELDING JOINT QUALITY IN STORAGE TANKS OF HAZARDOUS INDUSTRIAL FACILITIES USING MODERN NON-DESTRUCTIVE TESTING METHODS (Symposium on Natural and Applied Sciences, 2026)
Storage tanks used in hazardous industrial facilities are exposed to various operational loads, and the reliability of their welded joints directly affects the overall safety of the structure. This article examines the quality assessment of welded joints in storage tanks and analyzes the causes of defects that may occur during welding and operation. Particular attention is paid to the methods used for detecting welding defects, including visual inspection, ultrasonic testing, radiographic examination, and magnetic particle testing. The article concludes that regular inspection of welded joints, combined with proper maintenance and technical diagnostics, is necessary to ensure safe operation of storage tanks at hazardous industrial facilities.
Keywords: storage tank, welded joint, welding defects, non-destructive testing, ultrasonic testing, technical inspection, industrial safety, structural reliability.